Let's Go Home, Little Bear - Waddell, Martin; Nang ChanYeema (Cambridge, Massachusetts USA Candlewick Press, 1995)
When Little Bear is frightened by the noises he hears while walking in the snowy woods, his friend Big Bear reassures him.
Keywords: Story Collection